A review of printed passive electronic components through fully additive manufacturing methods. Issue 4 (1st October 2016) - Tan, H. W.; Tran, T.; Chua, C. K.
ABSTRACT: There have been significant advancements in the field of additive manufacturing in the past decades. Current technologies in this field allow fabrications of not only complex physical prototypes but also functional electronic components and circuitries. It is now possible to fabricate simple circuits embedded with several kinds of passive components, for example, resistors, capacitors, and inductors, which are the most fundamental building blocks of any electrical circuits. In order to aid future developments and integrations of printing electronics into a wider range of applications, this review attempts to provide an overview and the most recent developments of 'fully additive' printing techniques used for fabricating circuits and electronic components, including comparisons between their advantages and disadvantages. Each individual 'fully additive' printing technique is presented and discussed in detail. Potentials and challenges of additive manufacturing of electronics are also discussed.